Citizenship 2.0 dual nationality as a global asset - Harpaz, Yossi (Princeton studies in global and comparative sociology., 2019)
"The institution of citizenship has undergone significant change in the last two decades. Since the 1990s, dozens of countries have changed their laws to permit dual citizenship, moving away from the previous model that demanded exclusive allegiance. As a consequence, tens of millions of people around the world now hold citizenship in two (and sometimes three or four) countries. These changes have inevitably had an affect on the lived experience and personal meaning of citizenship, but the existing literature on dual citizenship has mostly focused on immigrants in Western Europe and North America and has inquired about identity and sentimental aspects of citizenship. Yossi Harpaz looks beyond the West in this book, arguing that the rise of dual citizenship has created new opportunities for non-Western elites to convert local advantages into a global resource. Millions draw on ancestral or ethnic ties to Western/EU countries or create such ties strategically in order to obtain a second nationality that will provide them with additional opportunities, an insurance policy, a high-prestige passport and even social status. He draws on qualitative and quantitative material from three cases that represent three pathways to compensatory citizenship: Hungarian-speaking Serbians who draw on their ethnicity to acquire a second citizenship from Hungary; upper-class Mexicans who engage in "birth tourism" in order to secure American citizenship for their children; and Israelis who reacquire the citizenship of European countries from which their parents and grandparents had immigrated half a century earlier"--